Role of ovarian artery-to-uterine artery anastomoses in uterine artery embolization: initial anatomic and radiologic studies - Ouyang, Zhenbo; Liu, Ping; Yu, Yanhong; Chen, Chunlin; Song, Xiaolei; Liang, Bo; Zhong, Guangming; Liu, Chang; Li, Zeyu (Surgical and radiologic anatomy (English ed.), 2012)
Purpose To explore the anatomic features of normal human ovarian artery-to-uterine artery anastomoses and their impact on uterine artery embolization (UAE). Methods Using slice computed tomography (CT) scanning and vascular casting; models of the uterine arterial vascular network were constructed using five sets of uterus, bilateral adnexa and vagina from normal adult females. The anatomy and characteristics of these models were then studied. Results Both the casting specimen and the CT-reconstructed model showed the ovarian artery-to-uterine artery anastomoses clearly. Each was composed of the ovarian branch of the uterine artery and the ovarian branch of the ovarian artery. All 10 ovarian artery-to-uterine artery anastomoses were formed by direct connection between the ovarian branch of the uterine artery and the ovarian branch of the ovarian artery. Conclusions Thin slice CT scanning combined with vascular casting is a useful method to study the small arterial network. The anastomoses between the ovarian branch of the uterine artery and the ovarian branch of the ovarian artery were formed mainly by direct connection. The implications of the ovarian artery-to-uterine artery anastomoses on UAE are unclear; further function assessments are needed.